2011
DOI: 10.1021/ol2001057
|View full text |Cite
|
Sign up to set email alerts
|

Expedient and Practical Synthesis of CERT-Dependent Ceramide Trafficking Inhibitor HPA-12 and Its Analogues

Abstract: The practical stereodivergent route to both syn- and anti-diastereomers of 1-substituted 3-aminobutane-1,4-diols based on the crystallization-induced asymmetric transformation (CIAT) approach was completed. This led to the revision of the reported stereochemistry of the first inhibitor of CERT-dependent ceramide trafficking HPA-12 from (R,R)-anti- to the (R,S)-syn-enantiomer. Due to the expeditiousness of production and inexpensive conditions developed, a series of alkyl- and aryl-substituted analogues of HPA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The N-Boc groups were removed by treating 2a with HCl (10%) in ethyl acetate and the crude hydrochloride salt was acylated using lauryl chloride (NaHCO 3 , THF, 0°C) to give 6a in 70% overall yield (Scheme 4) and the structure was confirmed by comparing the spectroscopic data with those reported in the literature. 10,12 This provides an easy and effective route for the synthesis of HPA-12 starting from benzaldehyde and L-serine. The other amino alcohols 2b-g were also treated similarly to give analogues of 6a (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-Boc groups were removed by treating 2a with HCl (10%) in ethyl acetate and the crude hydrochloride salt was acylated using lauryl chloride (NaHCO 3 , THF, 0°C) to give 6a in 70% overall yield (Scheme 4) and the structure was confirmed by comparing the spectroscopic data with those reported in the literature. 10,12 This provides an easy and effective route for the synthesis of HPA-12 starting from benzaldehyde and L-serine. The other amino alcohols 2b-g were also treated similarly to give analogues of 6a (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent report on the synthesis of HPA-12 by Berkeš et al, the potent molecule was shown to have a (1R,3S)-configuration, which is contrary to the initial reports. 10 The revised structure was confirmed using X-ray crystallographic analysis by Kobayashi et al 11 Thus the revised structure of HPA-12 has a syn-orientation of the amino and hydroxyl groups and hence methodologies for its synthesis should rely on syn-stereoselective reduction of the corresponding oxo-amino compounds. Recent reports on the synthesis of the (1R,3S) derivative of HPA-12 include a tandem approach using (S)-Wynberg lactone by Snowden et al, 12 Ru-catalyzed asymmetric rearrangement of isoxazolidines reported by Kang et al, 13 and the synthesis of HPA-12 and its analogues from serinol by Arenz et al 14 …”
Section: Introductionmentioning
confidence: 90%
“…(412) N-(3-Hydroxy-1-hydroxymethyl-3-phenylpropyl)dodecanamide (HPA-12 34 ) (see comment on stereochemistry)(413) inhibits ceramide trafficking by CERT. (414)…”
Section: Sphingolipid Metabolic Pathwaysmentioning
confidence: 99%
“…- The third is similar to the second, but the two direct nitro-Mannich products A and B with the observed configurations at the 6 position preferentially lactamise, and there is a postcyclisation epimerisation at the stereogenic carbon bearing the nitro group allowing equilibration to the (likely) most thermodynamically stable product (thermodynamic control, Path B) or a crystallisation-induced diastereoselectivity to give products 2 or 2’ with the nitro group occupying an axial or equatorial position, respectively [104–108] (Scheme 6, Path B/B’).…”
Section: Resultsmentioning
confidence: 99%